Effect of uranium deficiency on normal and superconducting properties in unconventional superconductor UTe2. (27th April 2022) - Haga, Y; Opletal, P; Tokiwa, Y; Yamamoto, E; Tokunaga, Y; Kambe, S; Sakai, H
Abstract: Single crystals of the unconventional superconductor UTe2 have been grown in various conditions which result in different superconducting transition temperature as well as normal state properties. Stoichiometry of the samples has been characterized by the single-crystal x-ray crystallography and electron microprobe analyses. Superconducting samples are nearly stoichiometric within an experimental error of about 1%, while non-superconducting sample significantly deviates from the ideal composition. The superconducting UTe2 showed that the large density of states was partially gapped in the normal state, while the non-superconducting sample is characterized by the relatively large electronic specific heat as reported previously.